Generation of surface waves through friction: FEM investigation. Issue 1 (15th March 2018) - Graf, Matthias
Abstract: Sliding friction between two bodies can generate elastic vibration. This study uses a finite‐element model comprising an elastic body sliding against a flat rigid surface with constant coefficient of friction. For the elastic body a structured topography is taken into account. The model shows traveling surface waves, which depend on the asperities of the sliding surface. It can be shown that the surface structure and its inertia are the cause for elastic waves in the contact region. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)